The Expanding of Consciousness, Integral Consciousness, and Conscious Evolution in Paule Marshall’s Fiction - Silvia Castro Borrego (Miscelánea: A Journal of English and American Studies, 2022)
Paule Marshall’s literary concerns cover key issues of the Black Diaspora such as Black consciousness and the search for wholeness. These two issues connect with the research about the different manifestations of consciousness carried out by scientists such as physicist Peter Russell, nurse Margaret Newman, philosopher Ken Wilber and psychologist Paloma Cabadas. In this essay, I contend that Marshall’s characters experience different aspects of consciousness that take them into a process known as the search for wholeness. Paule Marshall’s writings are also part of the Black Consciousness Movement, inquiring into epistemologies that have their roots in “the workable past”, creating emancipatory knowledge for afro-descendants. The methodology employed to read Marshall’s novels follows the conscious evolution paradigm put forward by psychologist Paloma Cabadas, and the integral consciousness model proposed by Ken Wilber. Both models offer valid routes for analyzing Marshall’s characters in the light of Newman’s concept of expanding consciousness.